К понятию статуса разговорной речи - Исаева, О.В. (Культура народов Причерноморья, 2002)
The concept of colloquial speech and the problem of the colloquial speech and the system of functional styles
correlation are examined in the work. The analysis of two opposite tendencies – compression and abundance is
made. Great attention is paid to the speech efforts saving principle.